Networks, platforms, and strategy: Emerging views and next steps - McIntyre, David P.; Srinivasan, Arati (Strategic Management Journal, 2017)
Research summary : A substantial and burgeoning body of research has described the influence of platform‐mediated networks in a wide variety of settings, whereby users and complementors desire compatibility on a common platform. In this review, we outline extant views of these dynamics from the industrial organization ( IO) economics, technology management, and strategic management perspectives. Using this review as a foundation, we propose a future research agenda in this domain that focuses the on the relative influence of network effects and platform quality in competitive outcomes, drivers of indirect network effects, the nature and attributes of complementors, and leveraging complementor dynamics for competitive advantage . Managerial summary : In many industries, such as social networks and video games, consumers place greater value on products with a large network of other users and a large variety of complementary products. Such “network effects” offer lucrative opportunities for firms that can leverage these dynamics to create dominant technology platforms. This article reviews current perspectives on network effects and the emergence of platforms, and offers several areas of future consideration for optimal strategies in these settings . Copyright © 2016 John Wiley & Sons, Ltd.